Time Pressure and In-group Favoritism in a Minimal Group Paradigm - Maeda, Kaede; Hashimoto, Hirofumi (Frontiers in Psychology, 2020)
Based on the group heuristic model and the model of intuitive cooperation, we hypothesized that in-group favoritism would be conspicuously shown through an intuitive process. To test this hypothesis, we utilized a minimal group paradigm, which is traditionally used in social psychological studies, and manipulated decision time in a one-shot prisoner’s dilemma game to compare the cooperative contribution level toward in-group and out-group members under three conditions: intuitive, empathic deliberation, and rational deliberation. Our findings confirmed that in-group favoritism was clearly shown in the intuitive condition only, suggesting that the intuitive cooperation model may only be valid in the context of social exchange with in-group members. Additional analysis also showed that in-group favoritism disappeared for participants who had been forced into empathic or rational deliberation for decision making. The theoretical implications of the findings are discussed.